EXPERT RESEARCH OF MEAT AND MEAT PRODUCTS - Гавриленко, О. С.; Хоміцька, О. А.; Загорулько, О. В. (Scientific Progress & Innovations, 2017)
The article contains research results of quality and safety of meat and sausages of Ukrainian producers on organoleptic, physical-chemical and microbiological parameters. We analysed basic parameters of safety products that are sold in the trading network. The results studies found the main causes of non-compliance under the current standards – a measure of total microbial contamination (MAFAM) and excess amounts of E. coli bacteria, indicating a violation of technological regimes and hygiene requirements of production, storage, transport and sale.